2007
DOI: 10.1160/th07-02-0132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with venous thromboembolism and renal insufficiency

Abstract: There is little information on the clinical outcome of patients with venous thromboembolism and renal insufficiency. RIETE is an ongoing, prospective registry of consecutive patients with acute, objectively confirmed, symptomatic deep vein thrombosis (DVT) or pulmonary embolism (PE). In this analysis we analyzed the three-month outcome in patients with creatinine clearance (CrCl) <30 ml/min. As of March 2007, 1,037 of the 18,251 (5.7%) patients enrolled in RIETE had CrCl <30 ml/min. During the three-month stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 14 publications
2
40
0
5
Order By: Relevance
“…Renal insufficiency was an individual predictor of PE related death at least in univariate analysis. These findings are supported by previous reports [22][23][24]. Based on the facts that the magnitude of NT-proBNP elevation is related to kidney function and that renal insufficiency predicts mortality, we conclude that the validity of NT-proBNP as a marker for short-term prognosis is decreased by renal dysfunction, as renal insufficiency itself may be a concurrent risk factor for PE-mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Renal insufficiency was an individual predictor of PE related death at least in univariate analysis. These findings are supported by previous reports [22][23][24]. Based on the facts that the magnitude of NT-proBNP elevation is related to kidney function and that renal insufficiency predicts mortality, we conclude that the validity of NT-proBNP as a marker for short-term prognosis is decreased by renal dysfunction, as renal insufficiency itself may be a concurrent risk factor for PE-mortality.…”
Section: Discussionsupporting
confidence: 91%
“…In the subgroup with an eGFR Ͻ30 ml/min (n ϭ 1037), the rates of major and fatal bleeding after 3 mo were 7.3 and 2.2%, respectively, which were significantly higher than the respective 2.1 and 0.5% in the group with an eGFR Ͼ30 ml/ min (n ϭ 17,214); however, the rates of embolic events, especially fatal pulmonary embolism, were also markedly higher in those with an eGFR Ͻ30 ml/min (6.4 versus 1.3%). 27 With regard to atrial fibrillation, one single-center report of patients with ESRD observed an annual rate of 11% for hemorrhages in patients who were not on anticoagulation, 16% in those treated with antiplatelet therapy, and 26% in those on oral anticoagulation. Of note, in 10 of the 13 patients who were on coumadin and had bleeding, the international normalized ratio (INR) was higher than intended (no values specified in the article), but none of the bleeding complications with oral anticoagulation was fatal.…”
Section: Oral Anticoagulationmentioning
confidence: 99%
“…[27][28][29] In the largest cohort of 123 patients who had ESRD with atrial fibrillation and were on oral anticoagulation, patients had significantly better overall long-term survival compared with those not treated, 21 whereas patients who had ESRD and sustained ischemic stroke had a dramatic 2-yr mortality rate of 75% ( Figure 1C). 1 Third, the risk for hemorrhages seems to be especially increased during the first 30 to 90 d after initiation of oral anticoagulation, 27,44,46,47 because initial therapy often results in INR values Ͼ3.0. 28,44 Moreover, these hemorrhages in the early phase may be caused by some patient-inherent factors, such as cerebral microangiopathy.…”
Section: Individual Risk Stratification As a Way Out Of The Dilemmamentioning
confidence: 99%
“…A recent prospective study on renal insufficient patients presenting a deep venous thrombosis and treated with anticoagulants (UFH, LMWH and/or VKA) showed that the main cause of death among them in the first three months of treatment was bleeding and not pulmonary embolism [14]. In studies comparing UFH and enoxaparin to fondaparinux, major bleeding was occurring in 1.1% of the patients treated by UFH (versus 1.3% for fondaparinux) [8], and 1.2% by the patients treated by enoxaparin (versus 1.1% for fondaparinux) [15].…”
Section: Discussionmentioning
confidence: 99%